What is the evidence for using antidepressants to reduce anxiety for people with dementia? - Joe Bingley; Amanda Young; Terence W.H. Chong (Archives of Gerontology and Geriatrics Plus)
Background: Antidepressants are frequently prescribed to alleviate the behavioural and psychological symptoms of dementia, including anxiety. However, their therapeutic value is uncertain. This review sought to clarify the evidence for the efficacy of antidepressants in reducing anxiety for people with dementia. Methods: A systematic search of Medline, EMBASE, APA PsycINFO, and the Cochrane Library was conducted on 25 July 2023 with keywords related to “antidepressants”, “dementia”, “anxiety”, and “Behavioral and Psychological Symptoms of Dementia” (BPSD). Included studies were randomised control trials, involved an antidepressant treatment arm, and reported pre- and post-treatment anxiety for people with dementia. Data were extracted from seven included studies, with major themes synthesised and described as a narrative review. Results: Five of seven trials found either no improvement in anxiety after antidepressant treatment, or no improvement compared to placebo. While two recent studies provide qualified support for citalopram, the generalisability of these findings is unclear, and target doses exceeded standard recommendations for prescribing in older adults. There is substantial heterogeneity between studies and just one used a specific measure of anxiety to detect changes. Conclusions: There is a paucity of evidence regarding the value of antidepressants for reducing anxiety in people with dementia. Qualified evidence suggests that citalopram, escitalopram, and other SSRIs may be most promising and warrant further investigation. Clinicians are encouraged to prescribe carefully and prioritise non-pharmacological approaches. Researchers are implored to systematically pursue effective, practical interventions for alleviating anxiety in people with dementia.